Customizing the microenvironment of CO2 electrocatalysis via three‐phase interface engineering. Issue 1 (30th March 2022) - Zhou, Xianlong; Liu, Hao; Xia, Bao Yu; Ostrikov, Kostya (Ken); Zheng, Yao; Qiao, Shi‐Zhang
Abstract: Converting CO2 into high‐value fuels and chemicals by renewable‐electricity‐powered electrochemical CO2 reduction reaction (CRR) is a viable approach toward carbon‐emissions‐neutral processes. Unlike the thermocatalytic hydrogenation of CO2 at the solid‐gas interface, the CRR takes place at the three‐phase gas/solid/liquid interface near the electrode surface in aqueous solution, which leads to major challenges including the limited mass diffusion of CO2 reactant, competitive hydrogen evolution reaction, and poor product selectivity. Here we critically examine the various methods of surface and interface engineering of the electrocatalysts to optimize the microenvironment for CRR, which can address the above issues. The effective modification strategies for the gas transport, electrolyte composition, controlling intermediate states, and catalyst engineering are discussed. The key emphasis is made on the diverse atomic‐precision modifications to increase the local CO2 concentration, lower the energy barriers for CO2 activation, decrease the H2 O coverage, and stabilize intermediates to effectively control the catalytic activity and selectivity. The perspectives on the challenges and outlook for the future applications of three‐phase interface engineering for CRR and other gas‐involving electrocatalytic reactions conclude the article. Abstract : Electrochemical CO2 reduction (CRR) takes place at the gas/solid/liquid three‐phase interface. Understanding of the microenvironment can provide additional opportunities to tune the CRR activity and selectivity. We critically examine the various methods of surface and interface engineering of the electrocatalysts to optimize the microenvironment for CRR, including the gas transport, electrolyte composition, controlling intermediate states, and catalyst engineering.